Exploring the Impact of Gamification on Student Engagement and Motivation in Higher Education Contexts - ZE, CHEN (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
With the continuous progress and innovation of educational technology, the emerging teaching mode of gamification has gradually attracted the attention of educators. The main purpose of this paper is to deeply explore how to skillfully integrate gamification elements into teaching activities, so as to stimulate students’ enthusiasm for learning and enhance their sense of classroom participation. To achieve this goal, this paper adopts various research methods, such as literature review, case analysis and empirical research, and systematically proposes a series of practical gamification teaching strategies and implementation steps. Moreover, this paper also verifies and analyzes the effectiveness of these gamified teaching methods through specific teaching cases, thus providing strong theoretical support and practical guidance for educational practice. In the current education field, gamified teaching, as an innovative teaching method, is gradually becoming one of the important directions of educational reform. It makes the learning process by introducing elements and ideas to make the game design more interesting and engaging, thus helping students master knowledge and skills in a relaxed atmosphere. This paper aims to deeply analyze the theoretical basis of gamification teaching and propose the corresponding teaching strategies. The case analysis section introduces the successful gamification teaching examples in detail, showing how to effectively combine the gamification elements with the course content, as well as the impact of this combination on students' learning motivation and learning effect, which provides a scientific decision-making basis for educators. Finally, this paper hopes to provide a comprehensive set of theoretical frameworks and operational guidelines for educators, and help them to better use gamification in teaching practice, so as to improve the teaching quality and students' learning effect.